Judicial Activity in Turkestan under the Colonial Regime - Nigora Qudratillaevna Rahimjonova (International Journal on Integrated Education, 2021)
The article describes the changes, limitations and consequences of the judiciary in the colonial conditions of Turkestan in the late nineteenth and early twentieth centuries. The example of the national press of the period also shows the attitude of the official administration to the policies of the judiciary.